2016
DOI: 10.1007/s00261-015-0619-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of computed high b-value diffusion-weighted imaging on prostate cancer detection

Abstract: High b-value cDWI using ME, IVIM, and SE diffusion models provide better image quality, lesion conspicuity, and increased LBCR than high b-value aDWI. Using cDWI can potentially provide comparable sensitivity and specificity for detecting significant PCa as high b-value aDWI without increased scan times and image degradation artifacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…The mono-exponential model is simpler to perform, and evidence indicates that it performs as well or almost as well as the bi-exponential model for computed DWI ( 30 ). The study performed by Verma et al ( 31 ) showed that high b-value (2000 s/mm 2 ) computed DWI using mono-exponential model, intra-voxel incoherent motion model, and stretched exponential diffusion model provided better image quality and lesion conspicuity, and increased lesion-to-background contrast ratios, as compared with acquired DWI. However, there were no significant differences in the detectability of prostate cancer among the computed DWIs and acquired DWI.…”
Section: Appropriate Conditions For Computed Dwimentioning
confidence: 99%
“…The mono-exponential model is simpler to perform, and evidence indicates that it performs as well or almost as well as the bi-exponential model for computed DWI ( 30 ). The study performed by Verma et al ( 31 ) showed that high b-value (2000 s/mm 2 ) computed DWI using mono-exponential model, intra-voxel incoherent motion model, and stretched exponential diffusion model provided better image quality and lesion conspicuity, and increased lesion-to-background contrast ratios, as compared with acquired DWI. However, there were no significant differences in the detectability of prostate cancer among the computed DWIs and acquired DWI.…”
Section: Appropriate Conditions For Computed Dwimentioning
confidence: 99%
“…However, their study included only single breast cancer patients, and there was no direct comparison between the same b values of computed and acquired DWIs. Recently, two studies that directly compared acquired and synthetic high b‐value DWI in prostate cancer patients reported that synthetic high b‐value DWI yielded a higher lesion detection rate, better image quality, higher lesion conspicuity, and increased lesion‐to‐background contrast ratios . However, prostate MRI has a significantly smaller field of view, and prostate gland background tissue is relatively more homogeneous than that of the breast.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with those of previous studies comparing the diagnostic accuracy of synthetic and acquired high b-value DWI. Blackledge et al 29 31,32 However, prostate MRI has a significantly smaller field of view, and prostate gland background tissue is relatively more homogeneous than that of the breast. Moreover, the prostate gland is less prone to motion artifact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cDWI images compared to original DWI images at the same b-value featured a reduced artifact level with similar or better CR and CNR values without additional acquisition time on top of the scan time used to obtain DWI with standard b-values [10,12,15,17,21].…”
Section: Discussionmentioning
confidence: 99%